2014
DOI: 10.1016/j.jad.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of vulnerability factors in patients with persistent and remitting lifetime symptom course of depression

Abstract: BackgroundResearch has suggested fundamental differences between patients with persistent and those with remitting courses of depression. This study investigated whether patients with different lifetime symptom course configurations differ in early risk and cognitive vulnerability factors.MethodsPatients with at least three previous episodes who were currently in remission were categorized based on visual timelines of their lifetime symptom course and compared with regard to a number of different indicators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…The researchers proposed that experiential avoidance could be an integral factor affecting the course and comorbidity development of emotional disorders. Research has shown that a more persistent course of depression is linked to higher levels of experiential avoidance (Barnhofer et al, 2014). Psychological inflexibility was also higher with college students reporting current or lifetime history of depressive and anxiety symptomatology, and it was also associated with depression/anxiety comorbidity (Levin et al, 2014).…”
Section: Psychological Flexibility and Depressive Symptomsmentioning
confidence: 99%
See 3 more Smart Citations
“…The researchers proposed that experiential avoidance could be an integral factor affecting the course and comorbidity development of emotional disorders. Research has shown that a more persistent course of depression is linked to higher levels of experiential avoidance (Barnhofer et al, 2014). Psychological inflexibility was also higher with college students reporting current or lifetime history of depressive and anxiety symptomatology, and it was also associated with depression/anxiety comorbidity (Levin et al, 2014).…”
Section: Psychological Flexibility and Depressive Symptomsmentioning
confidence: 99%
“…Similar findings on the relationship between the earlier version of the AAQ and various psychological measures of psychopathology and well-being have been reviewed by . Lack of psychological flexibility has been associated with general risk for psychopathology (e.g., Chawla & Ostafin, 2007;Fledderus, Bohlmeijer, & Pieterse, 2010;, as well as to more specific distresses such as depressive symptoms (e.g., Barnhofer et al, 2014;Berking et al, 2009;Bjornsson et al, 2010;Spinhoven, Drost, de Rooij, van Hemert, & Penninx, 2014;Tull, Gratz, Salters, & Roemer, 2004), and comorbid depressive, anxiety and substance use issues (Levin et al, 2014). It has also been theorized to influence the development and maintenance of a variety of psychological problems as well as the deterioration of psychological wellbeing (Kashdan, Barrios, Forsyth, & Steger, 2006;Levin et al, 2014).…”
Section: Psychological Flexibility and Depressive Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, experiencing a greater number of depressive episodes influences the organization of striatal networks (Meng et al, 2014) and may be associated with impaired hippocampal activation during a recollection memory task (Milne, MacQueen, & Hall, 2012) and with selective deficits in down-regulating amygdala responses to negative emotional stimuli using reappraisal (Kanske, Heissler, Schönfelder, & Wessa, 2012), factors that also contribute to risk for relapse. Vulnerability for recurrence of depressive episodes has been found to be associated with poorer outcomes in patients with earlier onset of depression, with increased number and length of depressive episodes (Moylan, Maes, Wray, & Berk, 2013), and with history of childhood trauma (Barnhofer, Brennan, Crane, Duggan, & Williams, 2014). Thus, in such patients, longer and more frequent depressive episodes appear to increase vulnerability for further episodes, precipitating an accelerating and progressive course of illness, leading to functional decline.…”
Section: How the Neuroscience Of Depression Can Inform Assessmentmentioning
confidence: 99%